Appraising Neonatal Morbidity and Mortality in a Developing Country Categorized by Gestational Age Grouping and Implications for Targeted Interventions - Mokuolu, Olugbenga Ayodeji; Adesiyun, Omotayo Oluwakemi; Ibrahim, Olayinka Rasheed; Suberu, Habibat Dirisu; Ibrahim, Selimat; Bello, Surajudeen Oyeleke; Mokikan, Moboni; Obasa, Temitope Olorunshola; Abdulkadir, Mohammed Baba (Frontiers in Pediatrics, 2022)
Introduction Despite the relatively higher neonatal morbidity and mortality in developing countries, there are limited data on the detailed analysis of the burden in Nigeria. With a database of over 14,000 admissions, this study presents a compelling picture of the current trends disaggregated by their gestational age groups. It provides unique opportunities for better-targeted interventions for further reducing newborn mortality in line with SDG 3, Target 3.2. Methods This prospective observational study involved newborn babies admitted to the Neonatal Intensive Care Unit of the University of Ilorin Teaching Hospital, Kwara State, Nigeria, between January 2007 and December 2018. The outcome was the neonatal mortality rates. The exposure variables included birth weight, gestational age (preterm versus term), and clinical diagnosis. Frequencies were generated on tables and charts, and the trends or associations were determined. Results Of the 14,760 neonates admitted, 9,030 (61.2%) were term babies, 4,847 (32.8%) were preterm babies, and in 792 (5%) of the admissions, the gestational ages could not be determined. Males constituted a higher proportion with 55.9%, and the total number of deaths in the study period was 14.7%. The mortality ratio was highest among babies with a birth weight of less than 1,000 g (38.0%) and gestational age of less than 28 weeks (65.5%). The trend analysis showed that the mortality rate decreased from 17.8 to 13% over the 12 years, p-value < 0.0001. For term babies, mortality decreased by 45%, from 15.7% in 2007 to 8.7% in 2018, while the decline in mortality for preterm babies was 28.4%, from 25.7% in 2007 to 18.4% in 2018. For both categories, p-values were < 0.001. Regarding morbidity in term babies, asphyxia occurred in (1:3), jaundice (1:5), sepsis (1:6), and respiratory disorders (1:6) of admissions. For mortality, asphyxia occurred in (1:2), sepsis (1:5), jaundice (1:8), and respiratory disorders (1:10) of deaths. The leading causes of morbidity among preterm babies were asphyxia (1:4), sepsis (1:5), respiratory disorders (1:9), and jaundice (1.10). For mortality, their contributions were asphyxia (≈1:2); sepsis (1:5); respiratory disorders (1:9), and jaundice (1:10). Conclusion There was a marked improvement in neonatal mortality trends. However, severe perinatal asphyxia, sepsis, hyperbilirubinemia, and respiratory disorders were the leading conditions contributing to 75% of the morbidities and mortalities. Measures to further accelerate the reduction in neonatal morbidity and mortality are discussed.